2019
DOI: 10.1029/2018jc014686
|View full text |Cite
|
Sign up to set email alerts
|

Role of Greenland Freshwater Anomaly in the Recent Freshening of the Subpolar North Atlantic

Abstract: The cumulative Greenland freshwater flux anomaly has exceeded 5,000 km 3 since the 1990s. The volume of this surplus freshwater is expected to cause substantial freshening in the North Atlantic. Analysis of hydrographic observations in the subpolar seas reveals freshening signals in the 2010s. The sources of this freshening are yet to be determined. In this study, the relationship between the surplus Greenland freshwater flux and this freshening is tested by analyzing the propagation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 82 publications
6
74
0
Order By: Relevance
“…Additional validation of these findings was conducted through comparison with results of tracer experiments employing a 0.08° (~4.5‐km horizontal resolution) HYbrid Coordinate Ocean Model (HYCOM) model. The model details and passive tracer calculations are provided in Dukhovskoy et al (; this special issue). Since 1993, site‐specific passive tracers were released continuously at the mouths of the Mackenzie River, East Eurasian Rivers (Kolyma, Lena, and Khatanga), West Eurasian Rivers (Pyasina, Enisey, Ob, Pechora, and Sev.…”
Section: Discussionmentioning
confidence: 99%
“…Additional validation of these findings was conducted through comparison with results of tracer experiments employing a 0.08° (~4.5‐km horizontal resolution) HYbrid Coordinate Ocean Model (HYCOM) model. The model details and passive tracer calculations are provided in Dukhovskoy et al (; this special issue). Since 1993, site‐specific passive tracers were released continuously at the mouths of the Mackenzie River, East Eurasian Rivers (Kolyma, Lena, and Khatanga), West Eurasian Rivers (Pyasina, Enisey, Ob, Pechora, and Sev.…”
Section: Discussionmentioning
confidence: 99%
“…As can be seen in Figures 11 and 16, runoff is included as a climatological mean based only on observations of river runoff. Dukhovskoy et al (2019) suggested that Greenland ice sheet and land ice melting, as compiled by Bamber et al (2012, 2018), is a potentially important source contributing to the recent freshening observed in the SPNA. Other studies, however, show that the freshwater source from Greenland ice sheet melting is relatively small, for example, as quantified in Haine et al (2015) or simulated in Böning et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…As all outflows from the Arctic Ocean lead to the SPNA and NSEA, it is expected that some of the associated freshwater will eventually be transported to these regions, for the SPNA to the western part in particular, which includes the Labrador Sea (LSEA). Furthermore, the Greenland ice sheet is losing mass at an accelerating rate (Bamber et al, 2012; Rignot et al, 2008; Trusel et al, 2018) providing additional freshwater into the SPNA and NSEA regions (Bamber et al, 2018; Dukhovskoy et al, 2019). Future climate change is expected to further increase the freshwater fluxes into both the Arctic and North Atlantic, as the result of an intensification of the water cycle, loss of sea ice, and glacial melting (Durack et al, 2012; Held & Soden, 2006; Jahn & Holland, 2013; Koenigk et al, 2007; Lau et al, 2013; Nummelin et al, 2016; Rennermalm et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…2 and 3). Further, while the EGC can receive additional freshwater from enhanced Greenland ice-sheet melt, the volume of freshwater from ice sheet melt is small compared to Arctic freshwater sources, and cannot explain interannual variations in SPNA salinity 48 .…”
Section: Freshening Of the Eastern Subpolar Region In 2012-2016mentioning
confidence: 99%